A study of white etching crack formation by compression-torsion experiments - S. Averbeck; E. Kerscher (Fracture and Structural Integrity)
In this study, an attempt was made to recreate the bearing damage phenomenon “White Etching Cracks” with a simplified testing setup. Rolling contact fatigue conditions were simulated with in-phase and out-ofphase cyclic compression-torsion experiments on 100Cr6 steel specimens. The results are compared in terms of microstructural change. Focused Ion Beam and metallographic analysis reveal that a fine-grained, white etching zone formed in the vicinity of the fatigue cracks of specimens tested with the in-phase load pattern. In contrast, no such structures were found after testing the out-of-phase load pattern. The properties of the white etching zone are characterised in more detail and compared with White Etching Cracks